2018
DOI: 10.1007/s10585-018-9947-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases as first manifestation of advanced cancer: exploratory analysis of 459 patients at a tertiary care center

Abstract: Symptomatic brain metastases (BM) are a frequent and late complication in cancer patients. However, a subgroup of cancer patients presents with BM as the first symptom of metastatic cancer. Here we aimed to analyze the clinical course and prognostic factors of this particular BM patient population. Patients presenting with newly diagnosed BM without a history of metastatic cancer were identified from the Vienna Brain Metastasis Registry. Clinical characteristics and overall survival were retrieved by chart rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…Therefore, a major difference in the present cohort may be the high percentage of systemic treatments after BM therapy, previously reported as a positive prognostic factor [10]. In particular, patients with precocious and synchronous tumors received systemic treatment due to a previously untreated primary disease.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, a major difference in the present cohort may be the high percentage of systemic treatments after BM therapy, previously reported as a positive prognostic factor [10]. In particular, patients with precocious and synchronous tumors received systemic treatment due to a previously untreated primary disease.…”
Section: Discussionmentioning
confidence: 84%
“…In cancer patients, the impact of the timespan until they develop BM on their further survival is unclear. Only a few studies are dedicated to this topic [3,[8][9][10], and even fewer compare the actual points in time to one another [6,10]. In multivariate regression, only the post-therapeutic clinical status (hazard ratio (HR) 0.38 0.25-0.58 p < 0.0001) and systemic therapy (HR 0.48 0.37-0.63 p < 0.0001) remained as independent prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Different definitions of CUP have been used by different authors over the years, complicating the identification of a homogeneous entity in literature. BM-CUPs have been variably defined either as BM with no previously known cancer (i.e., BM as the first manifestation of a systemic cancer, with the primary site not always remaining unknown) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], BM in which the primary site has not been identified within a temporal interval from onset (more often 2–3 months) [ 14 , 15 , 16 , 17 , 18 ], or as BM with no primary tumour identified after standard or extensive work-up [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In some studies, the definition of CUP is not clearly stated [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Definition and Diagnosis Of Cupmentioning
confidence: 99%
“…Although the majority of studies did not report significant differences in survival between patients with BM of known or unknown origin [ 8 , 14 , 17 , 19 , 21 , 22 , 25 , 30 , 66 , 67 ], older studies reported a better overall outcome in BM-CUP ascribed to the lack of a significant extracranial tumour burden [ 10 , 18 ]. In a recent study by Füreder et al [ 24 ], patients with BM-CUP showed a better survival when the primary was identified (after a latency of > 3 months). This was attributable to late systemic progression and the feasibility of tumour-specific chemotherapy.…”
Section: Managementmentioning
confidence: 99%
“…This wide range of outcomes exemplifies the need to obtain further prospective epidemiological data and analysis including stratification of tumor types and treatment modalities as the management of most primary cancers has become varied and complex. Recently Fureder et al reported no statistical difference in survival between CUP and CKP patients within 3 months of presentation [ 16 ] adding further weight to the hypothesis that there is no difference in survival outcomes between CKP and CUP groups undergoing cranial metastasis excision [ 1 , 7 , 15 , 23 , 26 ]. Interestingly, one study points out that median survival was significantly higher for treated as opposed to untreated CUP patients (3.6 and 1.1 months, respectively; p = 0.0001) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%